Improved die assembly for gas‐assisted sheet extrusion using different up and down gas layer thicknesses. Issue 5 (8th March 2021) - Jiang, Shiyu; Liu, Hesheng; Huang, Xingyuan; Yu, Zhong; Wang, Ruizhe; Shangguan, Yuanshuo
Abstract: Gas‐assisted sheet extrusion is a promising and environment‐friendly method used in polymer processing. Insufficient gas intake due to the adherence of the polymer melt to the inlet gap is a disadvantage of the method. Therefore, in this study an improved die assembly with parallel gas intake was designed. As the melt is prone to falling at the die exit during the horizontal extrusion process, different thickness settings are used for the up and down gas layers (0.25 and 0.75 mm, respectively) to avoid this. For the improved die assembly, the gas inlet pressure may be varied systematically to study the mechanism of stable sheet extrusion. When the gas inlet pressure is 0.1 MPa, the melt can be extruded smoothly, and the extruded sheet surface is transparent and flat. However, when the optimum pressure is exceeded, the extruded sheet becomes twisted or even broken. Abstract : In this study, an improved die assembly with parallel gas intake was designed. As the melt is prone to falling at the die exit during the horizontal extrusion process, different thickness settings are used for the up and down gas layers (0.25 and 0.75 mm, respectively) to avoid this.